Library and information science : parameters and perspectives - McIntosh, Joyce, 1968- (CRC Press, Taylor & Francis Group : Apple Academic Press, 2011)
Library and Information Science: Parameters and Perspectives focuses on how libraries function today, covering the most significant aspects of the field. The book includes chapters on the digitization of library materials, how technology has changed the role of libraries and librarians, Google's book and information applications, library user fees, customer service in the library, teaching information literacy and research skills, and more. Readers receive a broad understanding of the roles and functions of libraries and librarians today.